Algumas reflexões acerca da educação e disciplinarização feminina nas obras de Nísia Floresta (1827-1856) - Menezes, Ana Kelly Cavalcante (2022)
The present work is the result of studies and reflections carried out since graduation, about the History of women, gender relations and the female condition in the most diverse aspects. This research aims to analyze the main works of the writer and poet Nísia Floresta and her contribution to female education during the 19th century, as well as to understand the normative discourse present in her books. It is also intended to understand the discourses about the female role and what was expected of such in a patriarchal society that still breathed what was left of Portuguese America. To this end, the numerous changes that preceded the period of the clipping were examined, such as: the expulsion of the Jesuits in 1759 and the reform carried out by the Marquis of Pombal between 1750-1777. Also considered was the decree of 1827, which made official the teaching of first letters to women, 19th century periodicals, the letters exchanged between Nísia Floresta and Augusto Comte, and the works “Direitos das mulheres e injustiça dos homens” (1832), “Conselhos à Minha Filha” (1945), “Fany ou o modelo das donzelas” (1847), “Discurso que a suas educandas dirigio N.F.B. Augusta” (1847) and “Opúsculo humanitário” (1953). In the course of this paper, there’ll be discussions about the trajectory of 19th century women, in an exercise with Comparative History, intertwine with questions raised by Nísia Floresta about a more egalitarian and liberating education.